Classical and Keynesian Employment Theories: A Reconciliation - Edwards, Edgar O. (Quarterly Journal of Economics, 1959)
I. Introduction, 407. — II. Keynes's treatment of labor supply, 409. — III. Sketches of classical and Keynesian employment theories, 410. — IV. A graphical formulation of aggregate demand and supply, 412; the aggregate supply curve, 412; the aggregate demand curve, 414; the aggregate diagram, 414. — V. The classical theory amended, 416. — VI. The Keynesian diagram amended, 418. — VII. Keynesian economics in a classical framework, 420; the aggregate demand curve established, 420; expectations, unintended investment and aggregate demand, 420; involuntary unemployment, 422; labor supply, 423; the interest effect, 424; the real balance effect, 424. — VIII. The introduction of monopolistic elements, 426. — IX. Conclusion, 427. <qd> “It is only natural that attempts have been made to place under the Keynesian postulate some kind of theoretical underpinnings which would bring the foundation of his analytical structure to the level of orthodox argument.”1 </qd>